SHARED CUSTODY - Lopes Schabbach, Rosilene (Revista Gênero e Interdisciplinaridade, 2024)
This paper analyzes shared custody in the context of Brazilian law, highlighting its legal and social implications. The research addresses the responsibilities of the family institution and the changes introduced by the new Code of Civil Procedure, seeking to promote a critical understanding of the topic. The methodology used is bibliographic in nature, based on doctrines relevant to the discussion.